2022
DOI: 10.1002/adfm.202206024
|View full text |Cite
|
Sign up to set email alerts
|

LiTaO3:Bi3+,Tb3+,Ga3+,Ge4+: A Smart Perovskite with High Charge Carrier Storage Capacity for X‐Ray Imaging, Stress Sensing, and Non‐Real‐Time Recording

Abstract: Developing X-ray or UV-light charged storage and mechanoluminescence (ML) materials with high charge carrier storage capacity is challenging. Such materials have promising utilization in developing new applications, for example, in flexible X-ray imaging, stress sensing, or non-real-time recording. Herein, the study reports on such materials; Bi 3+ , Tb 3+ , Ga 3+ , or Ge 4+ doped LiTaO 3 perovskite storage and ML phosphors. Their photoluminescence, thermoluminescence (TL), and ML properties are studied. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…3a, when monitored at λ em = 355 nm, the PLE spectrum shows a broad band in the 250–330 nm region peaked at 303 nm. In addition to the peak at 303 nm, when monitored at λ em = 725 nm, other two 1–39 peaks at 615 and 655 nm are observed, which are ascribed to the 2 P 1/2 → 2 P 3/2 transition of Bi 2+ . PL spectra at room temperature of Li x Y 0.995 GeO 4 :0.005Bi 3+ ( x = 0.898, 0.991, 0.994, 0.997, 1.000 and 1.003) are shown in Fig.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…3a, when monitored at λ em = 355 nm, the PLE spectrum shows a broad band in the 250–330 nm region peaked at 303 nm. In addition to the peak at 303 nm, when monitored at λ em = 725 nm, other two 1–39 peaks at 615 and 655 nm are observed, which are ascribed to the 2 P 1/2 → 2 P 3/2 transition of Bi 2+ . PL spectra at room temperature of Li x Y 0.995 GeO 4 :0.005Bi 3+ ( x = 0.898, 0.991, 0.994, 0.997, 1.000 and 1.003) are shown in Fig.…”
Section: Resultsmentioning
confidence: 93%
“…21 In 2022, Lyu et al reported the ML perovskite materials Bi 3+ , Tb 3+ , Ga 3+ , or Ge 4+ doped LiTaO 3 , and studied the force induced charge carrier storage phenomenon in detail. 22 The reports mentioned above have proved that Bi 3+ ion doped ML materials are feasible to a certain extent, and although theoretically possible, ML in the UV spectral band has not been achieved by the Bi 3+ ion yet.…”
Section: Introductionmentioning
confidence: 97%
“…In this work, we systematically studied pressure- and rate-dependent ML behavior of Mn 2+ , Eu 3+ co-doped ZnS at different compression rates by employing a dynamic diamond anvil cell (dDAC), lab-built microsecond time-resolved fluorescence, in situ high-pressure synchrotron X-ray diffraction (XRD), PL, and thermoluminescence. We chose Mn 2+ , Eu 3+ co-doped ZnS phosphor rather than ZnS: Mn 2+ , as the optical performance can be improved by co-doping transition-metal ions or rare-earth-metal ions to increase the defect concentration. ,, It is revealed that pressure and compression rate have great influence on the ML emission efficiency and wavelength via the pressure-induced enhancement of the interaction between the host lattice and doped luminescent ions. Our findings not only open a new door for exploiting the relationship between structural stability and optical performance under high pressure, as well as pressure- and rate-dependent ML, but also show the multifunctional potential applications of ZnS: Mn 2+ , Eu 3+ in new pressure sensors, dynamic pressure visualization, and stress distribution.…”
Section: Introductionmentioning
confidence: 99%
“…1 Due to the linear relationship between luminescence intensity and load, ML materials have potential applications in lighting and displaying, high-level information storage, artificial intelligent skin, health monitoring and wearable devices. [2][3][4][5][6][7][8] In particular, by using the luminescence signals as the medium, ML could enable in situ, remote, distributed and visualized stress sensing for different kinds of interfaces. 9 So far, ML has been classified into two categories of deformation-ML and tribo-ML (TML).…”
Section: Introductionmentioning
confidence: 99%
“…Thereinto, hosts with abundant intrinsic defects may be suitable for Tb 3+ ions to emit high intensity ML emissions, because it is generally acknowledged that both long persistent luminescence (PersL) and ML depend on defects to accommodate the carriers. 26 Therefore, deep defects in PersL materials can be directly used, and the ML performance can be enhanced by reasonably adjusting the defect concentration and distribution. 27 In recent years, research studies on LiYGeO 4 -based PersL materials have indicated that they have excellent PersLs with the afterglow time ranging from dozens of hours to hundreds of hours after irradiation by UV light.…”
Section: Introductionmentioning
confidence: 99%